Publishing Plates: Stereotyping and Electrotyping in Nineteenth-Century US Print Culture by Jeffrey M. Makala (review). - Cordell, Ryan (Early American Literature, 2024)
Jeffrey M. Makala's book "Publishing Plates: Stereotyping and Electrotyping in Nineteenth-Century US Print Culture" explores the transformative impact of stereotype and electrotype plates on book manufacturing technology in the 19th century. The book delves into the debates, disruptions, and socio-technical changes brought about by the adoption of these technologies, highlighting their role in reshaping the publishing industry and our understanding of intellectual property. Makala's work sheds light on how stereotype plates influenced literary culture, ownership of intellectual property, and the autonomy of marginalized authors, offering a valuable reference for scholars across subfields interested in the intersection of technology and publishing history.